We are Brothers United In a cammon Struggle President NYERERE To the Mozambican People - NYERERE, Julius Kambarage (Tanzania, 1975)
From the 30th of August to the 7 th of September the Mozambican people, organized by Frelimo, received With fraternal and militant enthusiasm the President of tanu and the united republic of Tanzania
Keywords: We are Brothers United In a cammon Struggle